The Next Generation of Rice: Inter-Subspecific Indica-Japonica Hybrid Rice - Zhang, Guiquan (Frontiers in Plant Science, 2022)
Rice (Oryza sativa) is an important food crop and has two subspecies, indica and japonica. Since the last century, four generations of rice varieties have been applied to rice production. Semi-dwarf rice, intra-subspecific hybrid rice, and inter-subspecific introgression rice were developed successively by genetic modification based on the first generation of tall rice. Each generation of rice has greater yield potential than the previous generation. Due to the stronger heterosis of indica-japonica hybrids, utilization of the inter-subspecific heterosis has long been of interest. However, indica-japonica hybrid sterility hinders the utilization of heterosis. In the past decades, indica-japonica hybrid sterility has been well understood. It is found that indica-japonica hybrid sterility is mainly controlled by six loci, S5, Sa, Sb, Sc, Sd, and Se. The indica-japonica hybrid sterility can be overcome by developing indica-compatible japonica lines (ICJLs) or wide-compatible indica lines (WCILs) using genes at the loci. With the understanding of the genetic and molecular basis of indica-japonica hybrid sterility and the development of molecular breeding technology, the development of indica-japonica hybrid rice has become possible. Recently, great progress has been made in breeding indica-japonica hybrid rice. Therefore, the indica-japonica hybrid rice will be the next generation of rice. It is expected that the indica-japonica hybrid rice will be widely applied in rice production in the near future.